2016
DOI: 10.5465/ambpp.2016.15919abstract
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of public support on inbound open innovation

Abstract: Applying several matching estimators to a sample of Spanish manufacturing SMEs, we evaluate the impact of regional and federal funding on inbound open innovation strategies. Such SMEs are more likely to respond to public support by increasing either their cooperation with government institutions or their investment in extramural R&D than by enhancing cooperative networks. A policy corollary is to promote measures to attenuate cooperation failures. Methodologically, each type of funding and each type of coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Czarnitzki and Delanote (2015) evaluated the EU policy on independent young SMEs in high tech sectors and found that current policy focus is not ineffective. Positive effects of R&D subsidies were also found by Douglas et al, 2016 who analyzed the treatment effect on a wide range of innovation output in European SMEs. They found positive effects of the innovation support program, typically increasing the probability of innovation and its commercial success by around 15 percent.…”
Section: Randd Subsidy and Output Additionalitymentioning
confidence: 74%
See 1 more Smart Citation
“…Czarnitzki and Delanote (2015) evaluated the EU policy on independent young SMEs in high tech sectors and found that current policy focus is not ineffective. Positive effects of R&D subsidies were also found by Douglas et al, 2016 who analyzed the treatment effect on a wide range of innovation output in European SMEs. They found positive effects of the innovation support program, typically increasing the probability of innovation and its commercial success by around 15 percent.…”
Section: Randd Subsidy and Output Additionalitymentioning
confidence: 74%
“…The implication of these findings is that R&D subsidy for venture firms does not relieve the burden of liability of newness and smallness of venture firms, especially the disadvantage in market penetration and competition. It suggests, thus, that further policy measures are implemented so as to identify and eliminate barriers to market acceptance for new products of venture firms (Douglas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%